MicroRNA-132 regulates quinolinic acid production in the brain during LPS-induced neuroinflammation - Amir Mohamed Kezai; Amir Mohamed Kezai; Papa Yaya Badiane; Benjamin Hennart; Delphine Allorge; Sabrina Marion; Sébastien S. Hébert; Sébastien S. Hébert (Frontiers in Immunology)
BackgroundThe kynurenine pathway (KP) plays a major role in neuroinflammation by converting the amino acid tryptophan into a variety of neuroactive products, including neurotoxic quinolinic acid (QUIN). The gene expression regulatory role of microRNAs in neuroinflammation is well documented; however, their impact on KP in the brain remains unexplored.MethodsIn this study, we investigated whether the neuroimmune miR-132/212 cluster regulates one or more members of the KP during lipopolysaccharide (LPS)-induced neuroinflammation in vivo in mice and in vitro in BV-2 microglial cells.ResultsIn wildtype mice, we demonstrated that a subtoxic dose of LPS triggers a significant neuroinflammatory response with upregulation of KP enzymes, particularly kynurenine 3-monooxygenase (KMO), a key enzyme in QUIN synthesis, leading to elevated brain levels of this neurotoxic metabolite. Interestingly, KMO expression and activity remained elevated in miR-132/212 knockout mice after post-inflammation resolution. In vitro experiments using BV-2 microglial cells showed that miR-132 overexpression led to downregulation of KMO expression and enzyme activity and reduced QUIN levels without altering the microglial activation status.ConclusionCollectively, these findings suggest that the miR-132/212 cluster functions as a novel modulator of KP metabolism during LPS-induced inflammation, and acts as a potential therapeutic target for controlling neurotoxic QUIN accumulation in neuroinflammatory conditions.